ANALISIS HAZARD GEMPA DKI JAKARTA METODE PROBABILISTIK DENGAN PEMODELAN SUMBER GEMPA 3 DIMENSI - Yunalia Muntafi; Widodo Pawirodikromo; Lalu Makrup (TEKNISIA, 2015)
History records that Jakarta as the capital of Indonesia ever rocked by a devastating earthquake in 1699, 1780, 1883 and 1903, resulting in loss of physical, mental and material. The existence of several active faults around Jakarta potentially be the source of the earthquake that shook Jakarta. Therefore, the analysis of seismic hazard for Jakarta area is needed. The study was conducted by the method of Probabilistic Seismic Hazard Analysis (PSHA) with 3D modeling of seismic source and latest attenuation equations (Next Generation Attenuation) in accordance with the method used in the manufacture of the latest earthquake map (Earthquake Hazard Map of Indonesia 2010). The aims of this research are to (1) conduct hazard analysis seismic probabilistic as a reference value of the intensity of the hazard seismicity, (2) analyze deagragasi as early determinant of modification recording time history seismic acceleration corresponding to Jakarta bedrock and (3) analyze the spectral matching which then carried the ground motion design for Jakarta. The results of seismic hazard analysis shows that maximum acceleration at bedrock (PGA) for the Jakarta area with 500-year return period amounted to 0.236 g still in the range of PGA Jakarta by Indonesian Earthquake Hazard Map of latest ISO 1726-2012 (0.20g-0.25g). This value is close to the value of the Hutapea’s research results (2009), amounting to 0.239g. However, it is higher than the proposed PGA of Irsyam et al (2008) which amounted to 0.20g, and lower than the value of PGA on Indonesian earthquake map published by the USGS in which Jakarta was in the range of 0.245g - 0.326g. Based on the deagregation analysis, obtained two sets of real-time earthquake data, namely time history of Kocaeli earthquake in 1999 and Landers earthquake in 1992 to present megathrust and shallow crustal earthquake source, then by spectral matching analysis, obtained two synthetic ground motions for each seismic source mechanisms in the period of 0.2 sec and 1.0 sec for Jakarta.